The effect of uphill and downhill slopes on centre of pressure movement, alignment and shot outcome in mid-handicap golfers - Hiley, M. J.; Bajwa, Z.; Liang, Y.; Blenkinsop, G. M. (Sports Biomechanics, 2021)
The aim of the study was to examine changes in centre of pressure (COP) movement, alignment and shot outcome during golf shots from flat, uphill, and downhill slopes by mid-handicap golfers. Twelve male golfers hit balls with a six-iron from the flat and 5° slopes while kinematics and kinetics of the swing were collected. A launch monitor measured performance outcomes. A shift in the COP was found during the backswing when playing on a slope, but disappeared during the downswing. Golfers attempted to align the body perpendicular to the slope at the start of the swing resulting in COP movement towards the lower foot, but were not able to maintain this throughout the swing, like low handicap golfers. There was no significant difference in stance width, but golfers placed the ball closer to the uphill foot on a slope. Ball speed was not significantly affected by the slope, but launch angle and ball spin were. Golfers were more likely to hit shots to the left from an uphill slope and to the right for a downhill slope. No consistent compensatory adjustments in alignment at address were found, with differences in final ball position due to lateral spin.